Emotional Intelligence and its Adolescents Being an Exemplary (Eurasian Journal of Learning and Academic Teaching, 2022)
This article focuses on the formation of emotional intelligence in adolescence and its psychological characteristics. Interrelated aspects of emotional-volitional and cognitive processes in adolescence are studied and the levels of emotional intelligence are described separately